Social welfare policies in non-democratic regimes: the development of social insurance schemes in Franco's Spain (1936-1950) - Álvarez Rosete, Arturo (2003)
In the 1930s and 1940s, different social welfare models were at the disposal of policy-makers of non-democratic countries. However, although social security models were being debated and advocated by experts and policy-makers, the non-democratic regimes of Latin America and Southern Europe only set up limited social insurance schemes aimed at protecting particular groups of people, resulting in very fragmented management systems.